2021
DOI: 10.3390/biom11121772
|View full text |Cite
|
Sign up to set email alerts
|

The ANXA2/S100A10 Complex—Regulation of the Oncogenic Plasminogen Receptor

Abstract: The generation of the serine protease plasmin is initiated by the binding of its zymogenic precursor, plasminogen, to cell surface receptors. The proteolytic activity of plasmin, generated at the cell surface, plays a crucial role in several physiological processes, including fibrinolysis, angiogenesis, wound healing, and the invasion of cells through both the basement membrane and extracellular matrix. The seminal observation by Albert Fischer that cancer cells, but not normal cells in culture, produce large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 219 publications
(280 reference statements)
1
6
0
Order By: Relevance
“…In epithelial cancers, epithelial-to-mesenchymal transition (EMT) has been linked to growth along blood vessels [48]. In accordance, we found intriguing overlaps between previously described regulators of EMT and genes detected in ANXA1-positive cells, including TCF4 [45, 46], and S100A10 [49]. Future research endeavors include delineating regulatory dependencies and exploring the efficacy of targeting ANXA1 with small peptides [50] or exploiting it as a surface antigen for perivascular invading GBM cells.…”
Section: Discussionsupporting
confidence: 75%
“…In epithelial cancers, epithelial-to-mesenchymal transition (EMT) has been linked to growth along blood vessels [48]. In accordance, we found intriguing overlaps between previously described regulators of EMT and genes detected in ANXA1-positive cells, including TCF4 [45, 46], and S100A10 [49]. Future research endeavors include delineating regulatory dependencies and exploring the efficacy of targeting ANXA1 with small peptides [50] or exploiting it as a surface antigen for perivascular invading GBM cells.…”
Section: Discussionsupporting
confidence: 75%
“…S100A10 has been reported to promote tumor progression and metastasis by regulating multiple signaling pathways related to cell migration, invasion, metastasis, and angiogenesis [22]. S100A10 is known for its role in interacting with ANXA2 to form the ANXA2/S100A10 heterotetrameric complex (AIIt), which is identified as one of the oncogenic plasminogen receptors [23]. The activation of plasminogen by AIIt not only activates pro-matrix metalloproteinases (pro-MMPs) but also induces the angiogenesis of cancer stroma via ECM-associated proangiogenic growth factors, which both play an important role in the invasion and metastasis of cancer [7].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that phosphorylation at Tyr23 of ANXA2 is important for its extracellular translocation, and ANXA2 is a substrate of Src kinase ( 34 , 35 ). Therefore, we next wanted to know whether PRV infection can modify the phosphorylation of ANXA2 and Src kinase activity.…”
Section: Resultsmentioning
confidence: 99%